2018
DOI: 10.3892/or.2018.6710
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of genome-wide profiles coupled with Connectivity Map database mining to identify potential therapeutic targets for cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is one of the most common epithelial cell malignancies worldwide. However, its prognosis is poor. The aim of the present study was to examine the prognostic landscape and potential therapeutic targets for CCA. RNA sequencing data and clinical information were downloaded from The Cancer Genome Atlas (TCGA) dataset and processed. A total of 172 genes that were significantly associated with overall survival of patients with CCA were identified using the univariate Cox regression method. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…This finding indicates that the stronger association obtained from the G2/M gene signature might result from the interaction of these genes in the regulation of the G2/M cell cycle. In concordance with our study, previous studies have demonstrated a correlation between high PLK1 expression and unfavorable prognosis in CCA patients as well as the effectiveness of inhibiting PLK1 in CCA cells [ 56 , 57 , 58 ]. While PLK1 inhibitors such as BI2536 and GW843682X have been predicted to be effective drugs for CCA patients with a poor prognosis [ 59 ], PLK1 inhibitors such as NMS-1286937 (onvansertib) and BI2536, BI6727 (volasertib) have been evaluated in clinical trials and are generally well-tolerated, and their clinical efficacy is partially responsive with a monotherapy, particularly in cancers at advanced stages [ 60 ].…”
Section: Discussionsupporting
confidence: 93%
“…This finding indicates that the stronger association obtained from the G2/M gene signature might result from the interaction of these genes in the regulation of the G2/M cell cycle. In concordance with our study, previous studies have demonstrated a correlation between high PLK1 expression and unfavorable prognosis in CCA patients as well as the effectiveness of inhibiting PLK1 in CCA cells [ 56 , 57 , 58 ]. While PLK1 inhibitors such as BI2536 and GW843682X have been predicted to be effective drugs for CCA patients with a poor prognosis [ 59 ], PLK1 inhibitors such as NMS-1286937 (onvansertib) and BI2536, BI6727 (volasertib) have been evaluated in clinical trials and are generally well-tolerated, and their clinical efficacy is partially responsive with a monotherapy, particularly in cancers at advanced stages [ 60 ].…”
Section: Discussionsupporting
confidence: 93%
“…Genomic sequencing studies in CCA have identified many driver gene alterations, such as in ELF3, ARID1 and ARID2 (6). Lin et al (7) previously screened survival-associated genes of CCA and found that genes were significantly enriched in the Wnt signaling pathway, the apoptotic process and a number of oncogenic pathways, which may be altered in patients with poorer survival. The target genes SGSH, EIF5A, BET1L, GCNT4 and PLCG2 were identified, which may be associated with the prognosis of CCA (8).…”
Section: Introductionmentioning
confidence: 99%
“…PLK1 is the most studied member of the PLKs family of Ser/Thr protein kinases, which represents a crucial player in managing multiple aspects of cell division, including genomic stability, mitotic entry and exit and cellular response to DNA damaging insults [167,168]. PLK1 has been described as overexpressed and associated with poor prognosis in a plethora of human neoplasms, including CCA [169][170][171]. Indeed, hindering PLK1 by using blocking antibodies, genetic depletion and pharmacological molecules negatively affects cancer cell proliferation and results in the induction of apoptosis [169].…”
Section: Plk1mentioning
confidence: 99%